The Evaluation of Elite Karate Development Program in PPLP (Students’ Sport Training and Education Center) of Southern Sumatera Province - Lestariani, Wulan Agustina; Rustiadi, Tri; Mukarromah, Siti Baitul (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
This research aims at analyzing and evaluatingthe developmental program of elite Karate in PPLP (Students’ Sport Training and Education Center). This research is an evaluation of a program by using Countenance Evaluation Model (Stake) reviewed from several stages: antecedent/context, transaction/process, and outcome. It means that this research is considered to have more accurate and objective information as well as having been compared to what had been achieved from the developmental program. The data were collected through observation, interview, and documentation from the coaches, committee, athletes, and parents. The qualitative analysis technique in this research was based on 4 components, namely: data collection, data reduction, datadisplay, and conclusion drawing. The results of this study indicate that the Antecedent program is a form of coaching program that has been proven in an effort to improve athlete achievement. The entire PPLP karate athlete development program has been going well. Based onTransaction evaluation, it can be revealed that the process within transaction evaluation has not been going well. The outcome of the karate performance coaching program at PPLP which was carried out in South Sumatra in terms of the results of the medals had slightly decreased. It can be concluded that the Antecedents in PPLP of South Sumatra have clear backgrounds and goals, the completeness of the tools and the coaching program is also clear and directed, Transaction in the PPLP karate athlete development program in South Sumatra can be said to be good although there are still deficiencies in its implementation obtained in this program in this case have not had satisfactory results. The athletes' achievements can be said to be unstable in terms of the medals in each championship annualy which tend to be inconsistent.